KONDISI pH TERHADAP DENITRIFIKASI AIR LIMBAH NITROGEN MENGGUNAKAN REAKTOR BERBAHAN ISIAN BATU BELERANG DAN BATU KAPUR - Hasanuddin . (Jurnal Inovasi, 2011)
Most of the agro-industry use of nitrogen compounds on the production process. Consequently, resulting of waste water containing nitrogen compounds is quite high. When the levels exceed the specified threshold, it will result environmental pollution. Therefore, it is necessary the waste water process should meet the standards of environmental quality standards. The purpose of this study is to determine the condition of waste water acidity (pH) of the nitrogen waste water denitrification used a reactor made of sulfur stone and limestone. The research methodology used the process of denitrification. Denitrification of waste water with concentrations of nitrate for about 2000 mg-N / L performed in the bioreactor filled with sulfur and limestone. Data analysis used tables and graphs. The results showed that fairly neutral pH conditions on average 7.12, was due to the limestone that serves as a buffer.